2020
DOI: 10.1021/acsomega.9b04410
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Various Zero-Valent Metal Nanoparticles on a Superabsorbent Polymer for the Removal of Dyes, Nitrophenol, and Pathogenic Bacteria

Abstract: In this work, a superabsorbent polymer, sodium polyacrylate, also known as water ball (WB), loaded with Ni, Cu, and Ag zero-valent metal nanoparticles (MNPs) was applied for environmental remediation. WBs loaded with Ni, Cu, and Ag NPs were evaluated for their catalytic performance against the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) and decolorization of methyl orange (MO), Congo red (CR), and methylene blue (MB) dyes. The apparent rate constants (K app) for the reduction of 4-NP to 4-AP in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 60 publications
(94 reference statements)
2
18
0
Order By: Relevance
“…After this, 5 mg of Co/MA or Ni/MA was added to the reaction mixture and decrease in the peak intensity at 400 nm was recorded with reaction proceedings. It is worth to mention here that neither dyes nor PNP degraded alone with NaBH 4 as we mentioned in our previous reports that these reactions are thermodynamically favorable but not kinetically [2,10,45,46]. The Co/MA and Ni/MA converted the PNP in 12 min (Fig.…”
Section: Reduction Of Pnpmentioning
confidence: 57%
See 3 more Smart Citations
“…After this, 5 mg of Co/MA or Ni/MA was added to the reaction mixture and decrease in the peak intensity at 400 nm was recorded with reaction proceedings. It is worth to mention here that neither dyes nor PNP degraded alone with NaBH 4 as we mentioned in our previous reports that these reactions are thermodynamically favorable but not kinetically [2,10,45,46]. The Co/MA and Ni/MA converted the PNP in 12 min (Fig.…”
Section: Reduction Of Pnpmentioning
confidence: 57%
“…The resulting suspension was observed for UV-visible measurement in the range of 190-1000 nm. During the course of chemical reaction, a change in the color was observed in PNP or dye solutions [44]. The Co/MA catalytic activity was found highest against the degradation of PNP and MO as compared to Ni/MA; therefore, this catalyst was further used against the discoloration of CR, MB, and RB dyes.…”
Section: Catalysts Assessment Against the Degradation Of Selected Polmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the 4NP or dyes was treated with NaBH 4 , but no prominent changes were observed in their absorbance spectrum which suggested that the reaction is kinetically unfavorable. [ 26,32–34 ] Therefore, a catalyst is required to expedite the rate of reaction.…”
Section: Methodsmentioning
confidence: 99%